Predictors of functional impairment and awareness in people with dementia, mild cognitive impairment and healthy older adults from a middle-income country - Hartle, Larissa; Mograbi, Daniel C.; Fichman, Helenice Charchat; Faria, Camila Assis; Sanchez, Maria Angélica; Ribeiro, Pricila C. C.; Lourenço, Roberto Alves (Frontiers in Psychiatry, 2022)
Objective: To investigate the demographic, clinical and cognitive correlates of functional capacity and its awareness in people with dementia (PwD; n = 104), mild cognitive impairment (PwMCI; n = 45) and controls (healthy older adults; n = 94) in a sample from a middle-income country. Methods: Dementia and MCI were diagnosed, respectively, with DSM-IV and Petersen criteria. Performance in activities of daily living (ADL) at three different levels (basic [The Katz Index of Independence], instrumental [Lawton instrumental ADL scale] and advanced [Reuben’s advanced ADL scale]), measured through self- and informant-report, as well as awareness (discrepancy between self- and informant-report), were compared between groups. Stepwise regression models explored predictors of ADL and their awareness. Results: PwD showed impairment in all ADL levels, particularly when measured through informant-report. No differences were seen between controls and PwMCI regardless of measurement type. PwD differed in awareness of instrumental and basic, but not of advanced ADL, compared to controls. Age, gender, education and fluency were the most consistent predictors for ADL. Diagnosis was a significant predictor only for instrumental ADL. Awareness of basic ADL was predicted by memory, and awareness of instrumental ADL was predicted by general cognitive status, educational level, and diagnosis. Conclusions: Results reinforce the presence of lack of awareness of ADL in PwD. Use of informant-reports and cognitive testing for fluency are suggested for the clinical assessment of ADL performance. Finally, assessment of instrumental ADL may be crucial for diagnostic purposes.